Pequi Oil (Caryocar brasiliense Camb.) Attenuates the Adverse Effects of Cyclical Heat Stress and Modulates the Oxidative Stress-Related Genes in Broiler Chickens - Cruvinel, Jéssica Moraes [UNESP]; Groff Urayama, Priscila Michelin [UNESP]; Oura, Cássio Yutto [UNESP]; de Lima Krenchinski, Fernanda Kaiser [UNESP]; dos Santos, Tatiane Souza [UNESP]; de Souza, Beatriz Alves [UNESP]; Kadri, Samir Moura [UNESP]; Corrêa, Camila Renata [UNESP]; Sartori, José Roberto [UNESP]; Pezzato, Antonio Celso [UNESP] (MDPI, 2023)
The present study was conducted to determine the possible antioxidant protection of pequi oil (PO) against cyclic heat stress in broiler chickens and to highlight the application of PO as a promising additive in broiler feed. A total of 400 one-day-old male broiler chicks (Cobb 500) were randomly assigned to 2 × 5 factorially arranged treatments: two temperature-controlled rooms (thermoneutral—TN or heat stress—HS for 8 h/day) and five dietary PO levels (0, 1.5, 3.0, 4.5, or 6.0 g/kg diet) for 42 days. Each treatment consisted of eight replicates of five birds. The results showed that HS increased glucose (p = 0.006), triglycerides (p < 0.001), and HDL (p = 0.042) at 21 days and reduced (p = 0.005) serum total cholesterol at 42 days. The results also showed that HS increased the contents of alanine aminotransferase (ALT) and aspartate aminotransferase (AST). In contrast, PO linearly decreased AST (p = 0.048) and ALT (p = 0.020) at 21 and 42 days, respectively. The heterophil-to-lymphocyte ratio in the birds under HS was higher than in those in the TN environment (p = 0.046). Heat stress decreased (p = 0.032) the relative weight of their livers at 21 days. The superoxide dismutase activity increased (p = 0.010) in the HS treatments in comparison to the TN treatments, while the glutathione peroxidase activity in the liver decreased (p < 0.001) at 42 days; however, the activity of catalase had no significant effects. Meanwhile, increasing the dietary PO levels linearly decreased plasma malondialdehyde (p < 0.001) in the birds in the HS environment. In addition, PO reduced (p = 0.027) the expression of Hsp 70 in the liver by 92% when compared to the TN treatment without PO, mainly at the 6.0 g/kg diet level. The expression of Nrf2 was upregulated by 37% (p = 0.049) in response to PO with the 6.0 g/kg diet compared to the HS treatment without PO. In conclusion, PO supplementation alleviated the adverse effects of HS on broilers due to its antioxidant action and modulation of the genes related to oxidative stress, providing insights into its application as a potential feed additive in broiler production.
Keywords: antioxidant; broiler; carotenoids; oxidative damage; pequi